2020
DOI: 10.1186/s12889-020-08598-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and environmental determinants of child cognitive development in rural south africa and tanzania: findings from the mal-ed cohort

Abstract: Background: Approximately 66% of children under the age of 5 in Sub-Saharan African countries do not reach their full cognitive potential, the highest percentage in the world. Because the majority of studies investigating child cognitive development have been conducted in high-income countries (HICs), there is limited knowledge regarding the determinants of child development in low-and middle-income countries (LMICs). Methods: This analysis includes 401 mother-child dyads from the South Africa and Tanzania sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
3
8
0
1
Order By: Relevance
“…A recent follow-up of the MAL-ED cohort showed that socioeconomic status was associated with cognitive scores at 5 years 63 ; our study found a possible trend towards increasing MPI with a rise in socioeconomic scale.…”
Section: Discussionsupporting
confidence: 57%
“…A recent follow-up of the MAL-ED cohort showed that socioeconomic status was associated with cognitive scores at 5 years 63 ; our study found a possible trend towards increasing MPI with a rise in socioeconomic scale.…”
Section: Discussionsupporting
confidence: 57%
“…Mothers with higher education levels may have more knowledge of parenting, pay more attention to children's cognitive development, and improve their cognitive development through scientific methods [40,41]. The result of family income may be that the role of socioeconomic status on children's development gradually decreases with the development of social income [6,19]. We observed that paternal education was not statistically associated with suspected development delay.…”
Section: Discussionmentioning
confidence: 67%
“…This difference was 6.33 times more likely if there was an SP moment at 6 months. Children's cognitive development is influenced by several factors, including psychosocial exposures like parent-child interactions, cognitive stimulation and shared nurturing learning opportunities ( 86 ). The WHO's Nurturing Care Framework highlights the presence of bidirectional communication and enjoyable stimulating care as core to the provision of responsive care within a healthy mother–child relationship.…”
Section: Discussionmentioning
confidence: 99%